Importance of Hydrography in Resource Exploration - Abbasi, I. A. (The International Hydrographic Review, 2015)
Ever since man first ventured into the sea environment, hydrography has played a vital role in promoting marine scientific activities. This paper specifically deals with the importance of hydrography in resource exploration, highlighting the responsibilities of coastal States bordering the Indian Ocean to ensure availability of reliable and up-to-date nautical charts in order to derive maximum benefits from the regime created by the new United Nations Convention on the Law of the Sea. A brief summary is given of the approximate extent of the areas over which some of the States of the Indian Ocean will gain sovereign rights as soon as the new Convention, which is awaiting ratification, comes into force. A comparison of the EEZs with the land masses of a few countries reveals that they have gained control over areas much larger than the land. The status of hydrography and nautical charting of the countries concerned shows the enormous tasks that lie ahead for most of them to chart their waters as a matter of priority. The necessity for regional co-operation in hydrography and, finally, a brief on the IHO is included for the benefit of those who are not well aware of the activities of this unique and important intergovernmental organization serving the cause of hydrography since 1921.